2023
DOI: 10.1111/febs.16948
|View full text |Cite
|
Sign up to set email alerts
|

The interaction network of the proteasome assembly chaperone PSMD9 regulates proteostasis

Joel Christie,
C. Merlyn Anthony,
Mahalakshmi Harish
et al.

Abstract: Functional networks in cells are created by physical, genetic, and regulatory interactions. Mapping them and annotating their functions by available methods remains a challenge. We use affinity purification mass spectrometry (AP‐MS) coupled with SLiMFinder to discern such a network involving 26S proteasome non‐ATPase regulatory subunit 9 (PSMD9), a chaperone of proteasome assembly. Approximately 20% of proteins within the PSMD9 interactome carry a short linear motif (SLiM) of the type ‘EXKK’. The binding of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 81 publications
0
0
0
Order By: Relevance
“…PSMD9 is a companion to protease assembly. A cell knockout experiment confirmed that psmd9 plays a significant role in maintaining protein balance [ 16 ]. In addition, PSMD9 interacts with several free ribosomes subunits and plays a role in the transport of ribosomal proteins to the nucleolus, which helps to maintain the structure and morphology of the nucleolar membrane-free compartment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSMD9 is a companion to protease assembly. A cell knockout experiment confirmed that psmd9 plays a significant role in maintaining protein balance [ 16 ]. In addition, PSMD9 interacts with several free ribosomes subunits and plays a role in the transport of ribosomal proteins to the nucleolus, which helps to maintain the structure and morphology of the nucleolar membrane-free compartment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proteasome 26S Subunit, Non-ATPase 9 ( psmd9 ) is an active hub gene that links numerous pathways that are important for organelle structure, cell signaling, growth, survival and therapy resistance [ 16 ]. PSMD family members and their interacting molecules participate in the regulation of biological processes, such as the cell cycle, cell invasion and migration.…”
Section: Introductionmentioning
confidence: 99%